Monipar: movement data collection tool to monitor motor symptoms in Parkinson’s disease using smartwatches and smartphones - Sigcha, Luis; Polvorinos-Fernández, Carlos; Costa, Nélson; Costa, Susana; Arezes, Pedro; Gago, Miguel; Lee, Chaiwoo; López, Juan Manuel; de Arcas, Guillermo; Pavón, Ignacio (Frontiers in Neurology, 2023)
Introduction: Parkinson's disease (PD) is a neurodegenerative disorder commonly characterized by motor impairments. The development of mobile health (m-health) technologies, such as wearable and smart devices, presents an opportunity for the implementation of clinical tools that can support tasks such as early diagnosis and objective quantification of symptoms.Objective: This study evaluates a framework to monitor motor symptoms of PD patients based on the performance of standardized exercises such as those performed during clinic evaluation. To implement this framework, an m-health tool named Monipar was developed that uses off-the-shelf smart devices.Methods: An experimental protocol was conducted with the participation of 21 early-stage PD patients and 7 healthy controls who used Monipar installed in off-the-shelf smartwatches and smartphones. Movement data collected using the built-in acceleration sensors were used to extract relevant digital indicators (features). These indicators were then compared with clinical evaluations performed using the MDS-UPDRS scale.The results showed moderate to strong (significant) correlations between the clinical evaluations (MDS-UPDRS scale) and features extracted from the movement data used to assess resting tremor (i.e, the standard deviation of the time series: r=0.772, P<.001) and data from the pronation and supination movements (i.e, power in the band of 1-4 Hz: r=-0.662, P<.001).These results suggest that the proposed framework could be used as a complementary tool for the evaluation of motor symptoms in early-stage PD patients, providing a feasible and costeffective solution for remote and ambulatory monitoring of specific motor symptoms such as resting tremor or bradykinesia.